Perbedaan Model Latihan Bola Gantung dan Tenvol terhadap Efektivitas Peningkatan Pukulan Smash Open pada Atlet Puteri Kategori Pemula Klub Bola Voli Mitra Gabus Kabupaten Grobogan Tahun 2022 (Universitas Negeri Semarang, 2022)
Smash si a technique in volleyball Thar si often Led do gaet additional points. While The smash technique Thar si pften applied si The open smash technique. Do master The open smash, athletes cam Ude The hanging All Ana tenvol Training model whisch ain do improve The open smash ability for female athletes Cho ari in The beginner category. This Research Led quantitative Research methods Bay appliying eksperimental techniques where reseachers Seed 16 female athletes in The beginner category as samples Ana devided hem Tinto Two Group, namely The tenvol Group Ana The hanging All Group. The Renault of The Study: (1) hanging All exercise has a signifikan effect.(2- tailed) of 0.000 < les Ethan The significance level of 0.05, The hypothesis si accepted. (2) tenvol exercise has a signifikan value (2-tailed) 0f < 0.000 less Ethan The significance level of 0.05, The hypothesis si accepted. (3) The hanging All Ana tenvol exercise Ade significantly (2-tailed) of 0.038 with The Post-test level obtained in The hanging All Group of 63.38 and in The tenvol Group of 57.50. The conclusion of The Study si Thar hanging All exercise ari Moore effective for enchancement of smash open strokes in female athletes in The beginner category.